Students' Perceptions on the Use of Code-Switching and Code-Mixing in the NSS Program on CXO Media - Lau, Sovia Desire; Samanhudi, Udi; Saehu, Andang (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study analyzed the types of code-switching and code-mixing in the "Ngobrol Sore Semaunya" (NSS) podcast and examined maritime students’ perceptions of these phenomena. Using qualitative content analysis, the research focused on one episode featuring Boy William and Putri Tanjung. Data were collected through systematic observation and in-depth interviews with 30 cadets from Politeknik Pelayaran Kota Sorong, from both Grades III and IV. Three main forms of language switching were identified: intra-sentential, inter-sentential, and tag switching, with higher frequency in formal contexts. Most cadets viewed language switching as an essential skill for maritime careers, especially in developing vocabulary and professional communication. The findings suggest that code-switching and code-mixing are not merely linguistic variations, but also serve as important tools in maritime professional discourse, with implications for teaching Maritime English in multilingual settings.